Analysis of Physics Education Students Responses to the Development of Electronics Laboratory Guide Modules. - Ahda, Netriani Veminsyah; Utama, Tiara Hardyanti (Universitas Bengkulu, 2024)
The development of laboratory guide modules represents a strategic step in enhancing the quality of learning in physics education, particularly in electronics courses. This study aims to analyze students' responses to the development of modules based on a collaborative learning approach. Using a survey method involving 29 Physics Education students at Universitas Bengkulu, the results reveal that the developed module demonstrates advantages in terms of structure, language clarity, theoretical relevance, and the effectiveness of visual media. Additionally, the module is deemed capable of improving critical thinking skills, and problem-solving abilities, supporting the achievement of learning outcomes aligned with the syllabus. The average student response score falls into the